2017
DOI: 10.18632/oncotarget.15180
|View full text |Cite
|
Sign up to set email alerts
|

Idelalisib and bendamustine combination is synergistic and increases DNA damage response in chronic lymphocytic leukemia cells

Abstract: Idelalisib is a targeted agent that potently inhibits PI3Kδ which is exclusively expressed in hematological cells. Bendamustine is a well-tolerated cytotoxic alkylating agent which has been extensively used for treatment of chronic lymphocytic leukemia (CLL). Both these agents are FDA-approved for CLL. To increase the potency of idelalisib and bendamustine, we tested their combination in primary CLL lymphocytes. While each compound alone produced a moderate response, combination at several concentrations resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Previous studies have demonstrated synergy between IDE and BEN [17], IBR and BEN [18], or MK2206 (an inhibitor of AKT) and BEN [27]. Similarly, we have confirmed that IDE is synergistic with BEN, CLB and FLU in primary CLL cells occurring even in patients who were resistant to one agent.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Previous studies have demonstrated synergy between IDE and BEN [17], IBR and BEN [18], or MK2206 (an inhibitor of AKT) and BEN [27]. Similarly, we have confirmed that IDE is synergistic with BEN, CLB and FLU in primary CLL cells occurring even in patients who were resistant to one agent.…”
Section: Discussionsupporting
confidence: 84%
“…To determine if synergy was observed between the BCR pathway inhibitors and chemotherapy, as previously suggested [17], a matrix of dose combinations was created and observed cell death was compared to predicted cell death [19]. In 26 unique primary CLL samples, significant synergy was observed when combining BEN with IDE, using clinically relevant doses of each agent (5 µM for IDE and 10–20 µM for BEN; Figure 2A,B, red box) [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that in mantle cell lymphoma cell lines and patient-derived samples, idelalisib inhibits protein synthesis, which correlates with reductions in AKT (the immediate downstream effector of PI3K) and mitogen-activated protein kinase kinase (MEK) phosphorylation 85 . Idelalisib synergizes with bendamustine in primary CLL cells, increasing DNA damage and suppressing transcription of the anti-apoptotic protein myeloid cell leukemia 1 (MCL-1) 86 . Indeed, in a recently reported phase 3 trial (n = 416), the combination of idelalisib with BR markedly enhanced PFS in patients with R/R CLL (median of 20.8 versus 11.1 months for BR plus placebo after a median follow-up of 14 months) 87 .…”
Section: Targeting Phosphatidylinositol-3-kinase: Idelalisib and Newementioning
confidence: 99%